Uji Persamaan Simultan Free Cash Flow, Struktur Kepemilikan, Kebijakan Hutang, Kebijakan Dividen, dan Risiko dengan Kerangka Teori Keagenan dan Pensignalan - Muhammad`` Safiq; Liasari Liasari (Jurnal Ekonomi, 2020)
This study explores the use of simultaneous regression, this research aims to examine the interdependence relationship between free cash flow, debt policy, dividend policy, risk and structure of ownership in manufacturing companies in Indonesia. This research used six regression model to represent the interdependence relationship related to agency conflict and agency costs due to the difference in interest between agents (managers) and principals (managerial and institutional shareholders). Each regression model in this research is represent the conflicts of interest between the agent and the principal. This research extends Ismiyanti and Hanafi (2003). The result indicate an interdependence relationship between free cash flow, debt policy, and managerial ownership. This study also shows the effect of substitution between managerial ownership and debt policy in accordance with agency theory. It can be concluded that the managerial ownership may be able to reduce the use of debt in reducing agency conflicts between agents and principals.